2020
DOI: 10.4254/wjh.v12.i10.807
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sarcopenia on mortality in patients undergoing liver re-transplantation

Abstract: BACKGROUND Sarcopenia, which is a loss of skeletal muscle mass, has been reported to increase post-transplant mortality and morbidity in patients undergoing the first liver transplant. Cross-sectional imaging modalities typically determine sarcopenia in patients with cirrhosis by measuring core abdominal musculatures. However, there is limited evidence for sarcopenia related outcomes in patients undergoing liver re-transplantation (re-OLT). AIM To evaluate the risk of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…9 Lower muscle mass is also associated with a higher incidence of hepatic encephalopathy in patients with end-stage liver disease. 38,39 On the other hand, a group from USA 40 showed that sarcopenic patients had a higher tendency for pulmonary complications than the nonsarcopenic group (38% vs. 18%, P = 0.100); however, there was no significant difference in morbidity and mortality.…”
Section: Discussionmentioning
confidence: 98%
“…9 Lower muscle mass is also associated with a higher incidence of hepatic encephalopathy in patients with end-stage liver disease. 38,39 On the other hand, a group from USA 40 showed that sarcopenic patients had a higher tendency for pulmonary complications than the nonsarcopenic group (38% vs. 18%, P = 0.100); however, there was no significant difference in morbidity and mortality.…”
Section: Discussionmentioning
confidence: 98%
“…87 139 SMI was the most common parameter. Sarcopenia was associated with increased mortality, graft failure, reduced OS, and increased postoperative complications and infections in these studies, except for the study by Dhaliwal et al, 96 in which there was no difference in clinical outcomes between sarcopenic and nonsarcopenic patients. A study by van Vugt et al showed that sarcopenia is associated with increased health care costs and longer hospital stay following transplantation.…”
Section: Introductionmentioning
confidence: 85%
“…In this subgroup, there were 20 retrospective studies (4,168 patients) that assessed outcomes of sarcopenia in patients who underwent liver transplantation or had been waitlisted for the transplant procedure ( Table 5 ). 9 11 12 19 41 52 57 60 70 78 84 87 94 96 97 113 120 133 138 139…”
Section: Introductionmentioning
confidence: 99%
“…Psoas muscle area (PMA) was identified by CT or MRI scans gathered retrospectively within one year from the time when the DXA measurement was taken between the years 2018 and 2020 [ 19 ]. We calculated the mean area (mm 2 ) of both left and right psoas muscles from the middle of the third lumbar vertebra, so that both transverse processes were visible.…”
Section: Methodsmentioning
confidence: 99%